Unveiling the Anticarcinogenic Efficacy of Nirgundi with Emphasis on Oral Cancer: A Comprehensive Review - Ravi, Ashwini; V, Vasanthi; K B, Vinitha; Padmanabhan, Gopikrishna; Venkatkumar, Shruthi; K, Rajkumar (Asian Pacific Journal of Cancer Biology, 2024)
India contributes one-third to the global cancer burden, which may be attributed to the fact that the diagnosis is usually made in the advanced stage. Oral cancer is the most common cancer, predominantly caused by the use of tobacco in middle-aged males in India. The concept of chemotherapy initially emerged after systemic mustard gas poisoning damaged the bone marrow and lymphatic tissues. Traditional medicine has been proven to have medicinal value with fewer side effects as compared to allopathic drugs. Phytochemicals have been reported to exert anticancer effects by modulating the immune response and targeting the molecular mechanisms. Few studies have demonstrated that the traditional herbs exert antitumor efficacy by inducing cytotoxicity, promoting apoptosis, regulating epigenetic modifications, inhibiting metastasis along with their antioxidant and anti-inflammatory activity. Nirgundi (Vitex negundo) in various composition has been used in producing commercial pharmaceutical products for the management of both oral health and general health. The present review focuses on the antitumorigenic efficacy of Nirgundi in various cancers, with an emphasis on oral cancer.